Crosslinked cellulose dialdehyde for Congo red removal from its aqueous solutions. Issue 1 (March 2016) - Kumari, Sapana; Mankotia, Deepika; Chauhan, Ghanshyam S.
Graphical abstract: Highlights: Cellulose, extracted from pine needles, was crosslinked with epichlorohydrin. Crosslinked cellulose was converted to dialdehyde (CCDA) via periodate oxidation. CCDA was investigated as adsorbent for Congo red via the Schiff-base formation. Congo red removal was the highest at 60 min, 37 °C, pH 4.0 and 25 ppm. CCDA was reusable up to five repeat cycles and has MRC of 34.7 mg/g. Abstract: To realize the concept of e 2 (economy and environment protection), in the present study, pine needles, a forest biomass, was utilized as feedstock to extract cellulose for further functionalization via epichlorohydrin crosslinking and periodate oxidation to crosslinked cellulose dialdehyde (CCDA). The resultant material was well characterized by various techniques and investigated as an adsorbent for Congo red (CR), a carcinogenic diazo dye, via the Schiff-base formation. Parametric study of Congo red adsorption was carried out and the optimum time, temperature, pH and dye concentration were investigated. Furthermore, the maximum retention capacity and reusability of the candidate material was studied. The obtained data was analyzed on the basis of various kinetic and isotherm models. The CR adsorption on CCDA was observed to follow pseudo-second-order kinetics and Langmuir isotherm. The synthesized candidate material was reusable up to five repeat cycles and has maximum retention capacity of 34.7 mg/g.